PROYEKSI ANGKA KEJADIAN HIV/AIDS SAMPAI DENGAN TAHUN 2033 DI INDONESIA - Handayani, Lela; Oktriyedi, Ferly (Biro Akademik, Penelitian dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2024)
Reproductive Health is a state of complete physical, mental, and social well-being, not merely the absence of disease or infirmity in all matters relating to the reproductive system, functions, and processes. HIV and AIDS infection are also related to reproductive health. HIV cases in Indonesia have increased since 2010, peaking in 2017 before declining slightly in 2018. This increase reflects progress in early detection, but the spike in cases remains a challenge due to risky behavior, use of unsterile syringes, and population mobility. The majority of cases occur in men and the productive age group (25-49 years), with the main sources of transmission coming from unknown factors, MSM, and heterosexual intercourse. Affected professions include non-professional workers, housewives, and the self-employed, indicating that HIV is widespread in various levels of society. Projections show a downward trend in HIV, with a target of eliminating new cases by 2027. However, this achievement depends on the sustainability of effective prevention, early detection, and treatment programs as well as government and community support